2020
DOI: 10.1111/jcmm.14944
|View full text |Cite
|
Sign up to set email alerts
|

Defined host factors support HBV infection in non‐hepatic 293T cells

Abstract: Hepatitis B virus (HBV) is a human hepatotropic virus. However, HBV infection also occurs at extrahepatic sites, but the relevant host factors required for HBV infection in non‐hepatic cells are only partially understood. In this article, a non‐hepatic cell culture model is constructed by exogenous expression of four host genes (NTCP, HNF4α, RXRα and PPARα) in human non‐hepatic 293T cells. This cell culture model supports HBV entry, transcription and replication, as evidenced by the detection of HBV pgRNA, HBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…The results obtained by Yang et al, indicated that this cell culture model supports HBV entry, transcription, and replication, as evidenced by the detection of HBV pgRNA, HBV cccDNA, HBsAG, HBeAg, HBcAg and HBV DNA. Interestingly, these 293T-NE-3NRs cells were successfully infected with HBV even at low GEq which mimics natural physiological conditions more accurately [ 62 ]. Contrary to HBV, HDV does not seem to require the expression of these hepatocyte-enriched transcription factors.…”
Section: In Vitro Model Systems Based On Engineered Non-hepatic Cell Linesmentioning
confidence: 99%
“…The results obtained by Yang et al, indicated that this cell culture model supports HBV entry, transcription, and replication, as evidenced by the detection of HBV pgRNA, HBV cccDNA, HBsAG, HBeAg, HBcAg and HBV DNA. Interestingly, these 293T-NE-3NRs cells were successfully infected with HBV even at low GEq which mimics natural physiological conditions more accurately [ 62 ]. Contrary to HBV, HDV does not seem to require the expression of these hepatocyte-enriched transcription factors.…”
Section: In Vitro Model Systems Based On Engineered Non-hepatic Cell Linesmentioning
confidence: 99%
“…Yang et al . reported that infection of HEK293 cells with HBV requires the introduction of NTCP and at least three additional factors (HNF4a, PPARa and RxRa) 48 while this remains unknown for other, harder to transfect cell types. Using IVT mRNA may help to overcome this problem because it allows highly efficient introduction of multiple proteins simultaneously 26 or consecutively.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to HBV, HDV infection is predominantly determined at the receptor level [ 55 ]. Ectopic expression of human NTCP is enough to confer cells from different tissue and species susceptibility for HDV, whereas additional host factors besides NTCP are required for successful HBV infection [ 55 , 56 ]. HDV RNA replication is entirely independent of the helper virus.…”
Section: Helper Virus’s Functionsmentioning
confidence: 99%